Impacts of Surface Drag Coefficient and Planetary Boundary Layer Schemes on the Structure and Energetics of Typhoon Megi (2010) during Intensification - Coronel, Rochelle C (Archīum Ateneo, 2016)
The sensitivity of the simulated Typhoon Megi (2010) to frictional perturbations is studied by conducting experiments with the Deardorff planetary boundary layer parameterization. Here, we increase the surface drag by 50 % (Cd1.5) and change the scheme to Mellor-Yamada-Nakanishi-Niino Level 3 (MYNN) using the Meteorological Research Institute/Japan Meteorological Agency nonhydrostatic model. At 2-km horizontal resolution, the control run simulates deeper central pressure, and shallower maximum winds and inflow layer that are comparable to observations. In this study, Cd1.5 and MYNN are found to introduce substantial change on Megi’s low-level wind structures by disrupting the gradient-wind balance more than the control run. Increasing the surface drag reduces low-level tangential velocity and induces a stronger inflow near the surface and toward the center of the storm. This results in a narrow radius and lower height of the maximum tangential wind. On the contrary, the MYNN case increases the cyclone’s size and elevates the level of the induced inflow at the boundary layer, far from the center. From the energetics point of view, the impact of the imbalance introduced by the experiments during the initial stage of intensification is dual, i.e., while it enhances the generation of kinetic energy, it also amplifies frictional dissipation. In the kinetic energy equation, the induced inflow strengthens the secondary circulation, and subsequently, intensifies the dynamical energy conversion. On the other hand, our results illustrate that the mechanism for energy loss in Cd1.5 is significantly different from that in MYNN due to their different impacts on wind structures and momentum flux. Nevertheless, the increase in energy gain in both experiments is overweighed by the loss due to large dissipation of absolute angular momentum, leaving less kinetic energy for further intensification.